Simultaneous infection of healthy people with multiple human cytomegalovirus strains - Meyer-König, U; Ebert, Katja; Schrage, Birgit; Pollak, Stefan; Hufert, Frank T (The Lancet (British edition), 1998)
Meyer-Konig et al analyzed the distribution of human cytomegalovirus gB variants in different tissues from immunocompetent subjects.